2014
DOI: 10.1007/s00125-014-3211-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic neuropathy predicts renal function decline in patients with type 2 diabetes: a cohort study

Abstract: CAN was independently associated with CKD, albuminuria and eGFR in patients with type 2 diabetes. In addition, CAN was an independent predictor of the decline in eGFR over the follow-up period. CAN could be used to identify patients with type 2 diabetes who are at increased risk of rapid decline in eGFR, so that preventative therapies might be intensified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 44 publications
3
51
2
2
Order By: Relevance
“…Animal data support the role of increased sympathetic activity in the pathogenesis of renal disease (30). A recent study of adults with type 2 diabetes found that cardiac autonomic dysfunction was associated with increased albuminuria and lower eGFR at baseline and also predicted subsequent decline in eGFR (31). Clinical studies in adults with type 1 diabetes have been less clear on the role of cardiac autonomic function on renal decline (28,29,32).…”
Section: Discussionmentioning
confidence: 96%
“…Animal data support the role of increased sympathetic activity in the pathogenesis of renal disease (30). A recent study of adults with type 2 diabetes found that cardiac autonomic dysfunction was associated with increased albuminuria and lower eGFR at baseline and also predicted subsequent decline in eGFR (31). Clinical studies in adults with type 1 diabetes have been less clear on the role of cardiac autonomic function on renal decline (28,29,32).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, among normotensive patients with type 1 diabetes, individuals with CAN had higher nocturnal urinary albumin excretion attributed to an attenuation of nocturnal blood pressure dipping, which is a risk factor for progression of kidney disease (11, 29, 30). In a multiethnic cohort of 204 European and South Asian adults with type 2 diabetes, patients with CAN had lower estimated GFR and higher urinary albumin excretion (5). Similarly, we found negative associations between ACR and cardiac vagal function (E/I, sdNN, HF ratio) in the Pima Indians.…”
Section: Discussionmentioning
confidence: 99%
“…QT prolongation may lead to severe ventricular arrhythmias and a 2-fold risk of stroke [5]. There is emerging evidence that CAN is an independent predictor of the development and progression of diabetic nephropathy [6,7].…”
Section: Abbreviationsmentioning
confidence: 99%